2020
DOI: 10.1088/1742-6596/1444/1/012047
|View full text |Cite
|
Sign up to set email alerts
|

Comparison analysis of expanded polystyrene system (eps) and polyvinyl chloride (pvc) pipe as platform material of floating buildings in the coastal areas of Semarang

Abstract: The impact of tidal floods in the coastal area of Semarang greatly disrupts people’s activities and damages settlements and infrastructure buildings. Floating building is one of the alternative solutions to overcome the rising sea level. This study aims to compare 2 (two) floating housing material platforms, namely EPS (Expanded Polystyrene) and PVC (PolyVinyl Chloride). The analysis method of floating structure platform was carried out by using various indicators, namely, the uplift generated, the stability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The results of mycofoam molding showed that the mycelium could bind the substrate well in each formulation. Based on the characteristics after observation, mycofoam has several similarities with EPS, namely light, rigid, and brittle (Adi et al 2020). But the P1R formulation has the most similar appearance because the main substrate was sawdust which tends to have a smoother and flatter surface.…”
Section: Discussionmentioning
confidence: 99%
“…The results of mycofoam molding showed that the mycelium could bind the substrate well in each formulation. Based on the characteristics after observation, mycofoam has several similarities with EPS, namely light, rigid, and brittle (Adi et al 2020). But the P1R formulation has the most similar appearance because the main substrate was sawdust which tends to have a smoother and flatter surface.…”
Section: Discussionmentioning
confidence: 99%
“…A floating house with a styrofoam foundation design using styrofoam as its structural foundation can be a better choice in terms of buoyancy, stability and aesthetics. The styrofoam platform is more effective and efficient compared to PVC platform [3].…”
Section: Floating House Styrofoam Platformmentioning
confidence: 99%
“…Eco-friendly residence is really needed in areas affected by flooding and sea tides [2]. Fortunately, improvements in construction sector have introduced floating houses which may solve the problem [3]. The problem is the need of several design models and floating house prototypes that are eco-friendly, economical, aesthetically livable and can be applied in coastal areas [4].…”
mentioning
confidence: 99%
“…The impact will disrupt the activities of the population and make the settlement and infrastructure damaged. This makes a heavy loss for the government and people affected by rising sea levels [4].…”
Section: Introductionmentioning
confidence: 99%
“…A floating houses is a building structure that floats on water by relying on the weight of the area submerged as a load parameter that can be borne by the structure [1] [4]. Floating houses is one solution to prevent overcrowding in urban settlements.…”
Section: Introductionmentioning
confidence: 99%